Desenvolvimento de business intelligence na avaliação de desempenho em tribunais de contas brasileiros - LIMA, Saulo Coelho (Universidade Federal do Pará, 2022)
In a context of raised demand for public services, shortage of resources and increasing complexity of controlling these public resources within a perspective that considers the evolution of public administration, with the incorporation of concepts of governance, planning and social engagement, it is imperative to pursuit improvement of ours institutions through the perception of their actions. Performance evaluations are essential management tools that allow us to monitor the achievement of goals, identify advances, correct problems and the need to make changes. Aiming at the optimization proposal in the indicators evaluation process that establishes the measurement of performance, quality and agility of Court of Auditors’activities (established by ATRICON), applying a Business Intelligence tool that helps in the consolidation of the measurement of indicators and allows the registration and monitoring of the evolution of institution’s performance submitted to evaluation based on the framework Performance Measurement Milestone (MMD-QATC). To accomplish this task, the MySQL database management system was used in conjunction with HeidiSQL, the SQL Power Architect modeling tool, the Python programming language, the Pentaho Data Integration, part of the suite for BI solutions Pentaho in its Community Edition version, and the Microsoft Power BI Desktop. Thus, resulting in a more practical and scalable platform for consolidating the data.